Societal gender inequality and the gender gap in safety perceptions: Comparative evidence from the International Crime Victims Survey - Bhardwaj, Ntasha (European journal of criminology, 2022)
This study considers whether societal gender inequality moderates the relationship between gender and perceptions of personal safety. Pooled 1992?2005 rounds of the International Crime Victims Survey, comprising more than 285,000 respondents from 75 countries, are used to estimate multilevel models of safety perceptions, with a cross-level interaction specified between gender and gender inequality. We find that the gender gap in safety perceptions, although statistically significant in all countries, is largest in countries exhibiting high gender equality and smallest in countries with high gender inequality. This is explained entirely by variation in men?s safety perceptions; male respondents perceive themselves as safer in a milieu of gender equality, but less safe in a milieu of gender inequality. In contrast, the safety perceptions of female respondents are uncorrelated with societal gender inequality.